Stiffness and fracture analysis of photovoltaic grade silicon plates. (15th October 2016) - Zhao, Lv; Maynadier, Anne; Nelias, Daniel
Abstract: The rigidity and the strength of photovoltaic cells, particularly the centerpiece-embedded silicon plates, are of great importance from an economical point of view since their reliability impacts the overall cost based on production, transportation and in-service use. The present work focuses on the solar-grade multi-crystalline silicon used in PV wafers. The aim is to characterize the Young's modulus and to analyze the fracture behavior at room temperature. The Si plates have been laser cut from two different manufacturing processes of silicon wafers, MCSi and RST. Due to the brittle behavior of Si at ambient temperature, 4-point bending tests have been performed. The beam hypothesis has been used to analyze bending tests for determining the Young's modulus. A correction strategy has then been proposed with a numerical model in order to determine with a higher accuracy the mechanical data and the measurement uncertainty. For fracture investigation, high speed imaging technique and fractography have been used to identify the failure mode as well as the crack origin. The Young's modulus is found to be 166 ± 5 GPa for MCSi wafers. The anisotropic stiffness of RST plates is also revealed and correlates well with the micro-structural texture. Both kinds of plates fracture in trans-granular manner from the edges, where some defects are located due to laser cutting.